Zizo : magazine voor holebi's & transgenders. - Federatie Werkgroepen Homofilie (FWH) (Gent : FWH, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie: Kammerstraat 22, 9000 Gent
Nederlands
Periodiek